1998
DOI: 10.1128/jvi.72.5.3779-3788.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Herpes Simplex Virus Type 1 U L 17 Gene Encodes Virion Tegument Proteins That Are Required for Cleavage and Packaging of Viral DNA

Abstract: Previous studies have suggested that the UL17 gene of herpes simplex virus type 1 (HSV-1) is essential for virus replication. In this study, viral mutants incorporating either a lacZexpression cassette in place of 1,490 bp of the 2,109-bp UL17 open reading frame [HSV-1(ΔUL17)] or a DNA oligomer containing an in-frame stop codon inserted 778 bp from the 5′ end of the UL17 open reading frame [HSV-1(UL17-stop)] were plaque purified on engineered cell lines containing the UL17 gene. A virus derived from HSV-1(UL17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(39 citation statements)
references
References 41 publications
2
37
0
Order By: Relevance
“…The ability of the deletion virus to produce plaques on Vero cells suggested that UL21 is not needed for HSV-1, but it also provided evidence that the genes surrounding the U L 21 locus are functional. In particular, disruptions in the expression of any of the upstream, essential genes U L 15 (22), U L 17 (23), U L 18 (19), U L 19 (19), and U L 20 (24) are known to render the virus unable to make plaques on Vero cells. Similarly, disrupted expression of the downstream locus, U L 22, which encodes an essential entry glycoprotein (gH), would also render the ΔUL21 virus noninfectious on noncomplementing cells (25).…”
Section: Generation Of a U L 21 Deletion Virusmentioning
confidence: 99%
“…The ability of the deletion virus to produce plaques on Vero cells suggested that UL21 is not needed for HSV-1, but it also provided evidence that the genes surrounding the U L 21 locus are functional. In particular, disruptions in the expression of any of the upstream, essential genes U L 15 (22), U L 17 (23), U L 18 (19), U L 19 (19), and U L 20 (24) are known to render the virus unable to make plaques on Vero cells. Similarly, disrupted expression of the downstream locus, U L 22, which encodes an essential entry glycoprotein (gH), would also render the ΔUL21 virus noninfectious on noncomplementing cells (25).…”
Section: Generation Of a U L 21 Deletion Virusmentioning
confidence: 99%
“…In line with this, a PrV mutant lacking pUL25 forms mature capsids which accumulate in the nucleus in close apposition to the INM but are unable to bud (11). The role of the pUL17 component of the CVSC during nuclear egress is difficult to assess since it is also essential for the mechanistically coupled DNA-encapsidation process and its absence results in the formation of only immature B capsids which contain scaffold but lack viral genome and which are only inefficiently exported from the nucleus (12,13).…”
mentioning
confidence: 99%
“…Structural instability of capsids due to absent or reduced UL25 on capsids also appeared to change the property(ies) of capsids. In support of this suggestion, the absence or reduction in incorporation of UL25 into capsids, which can be caused by the UL25, UL17, and VP26 null mutations, produced improper localization of multiple capsid proteins (e.g., UL17, UL25, VP5, and VP22a) in discrete nuclear domains and appeared to induce aggregation of nuclear capsids (6,19,21,22,43). Previous studies were not able to determine whether the discrete nuclear domains with accumulations of multiple capsid proteins detected by immunofluorescence represent capsid aggregates or are aberrant accumulations of capsid proteins that have not formed capsid structures (6,19,21,22,43).…”
Section: Roles Of Hsv-1 Vp26 In Nucleocapsid Maturationmentioning
confidence: 85%
“…Journal of Virology the DNA concatemers were not cleaved, and only type B capsids were formed (6,(35)(36)(37)(38)(39)(40). Also, mutations in UL25 that preclude its binding to capsids were shown to exhibit the same phenotype as the UL25 null mutation (9), suggesting that UL25 functions in HSV-1 DNA genome packaging in capsids.…”
Section: Roles Of Hsv-1 Vp26 In Nucleocapsid Maturationmentioning
confidence: 99%
See 1 more Smart Citation